The characteristics of the Third Sector in Ukraine. Increases and decreases in the activity of particular organizations and the policy of the ruling elite - Pytlik, Kamila (Journal of Education Culture and Society, 2020)
The main subject of this article is the activity of non-governmental organizations in Ukraine and their role in the life democratization. The article includes methods of financing non-governmental organizations and the influence of domestic and foreign subsidies for their work. Moreover, it raises a question about ethical behaviour of people, that finance these organizations and reveals the political aspects of the decisions which were made.It depicts the development dynamics of NGOs during several years. Furthermore, it emphasizes the increase of activity of all members of the NGOs during the Orange Revolution and the stagnation caused by the political crisis in 2007. This work indicates what is the stimulus for the development of Ukrainian NGOs.